(untitled) (Bangladesh Journal of Obstetrics & Gynaecology, 2023)
Objective: First-time parenthood is a complex and emotional journey. The gap between demand and quality services for maternal, newborn and child health (MNCH) and family planning (FP) are significant. Lack of time, awareness, and social support are critical challenges of meeting the service requirement for the young and first-time mothers, especially working mothers in urban areas. Objective of the study was to design an intervention model for the young pregnant women and their partners for improving the quality and use of MNCH and FP services and information. Methods: Using a human-centered design (HCD) approach, we conducted 27 in-depth interviews, 10 focus group discussions, and eight mock sessions with first-time mothers, partners, family members, community influencers and service providers in Tongi, Gazipur. During phase 1, we explored the current realities of life and experience of services, both ideal and existing, from perspectives of a diverse set of stakeholders including both health care providers and care seekers. During phase 2, we designed, tested, and iterated the “group model” of antenatal Care through a series of mock sessions, interviews and consultation with service providers and authorities. We recorded, transcribed, and translated the data for collaborative synthesis and analysis process to generate insight and opportunities for optimizing service delivery and uptake. Results: The study findings spoke for the need of providing group sessions for first time parents, social support from peers and family members and capacity development of the service providers. After careful consideration of the stakeholder needs and preferences, the national guidelines and the local implementing partner’s available resources, we arrived at the recommended group model inclusive of five Group Antenatal Care (GANC) and two group Postnatal Care (GPNC) for mothers. All the pregnant women underwent through clinical checkups by medically trained professionals, mainly midwives and doctors. The group model also includes two GANC and one GPNC for fathers, as well as informative sessions for companions. The prototype model included five GANC and two GPNC sessions for mothers, two GANC and one GPNC session for fathers, and informative sessions for companions. The sessions included pregnant women of close gestational age, use of visual aids to support session facilitation, and activities to support group bonding and information retention. Conclusions: The Group Model offering 5 ANC and 2 PNC for women, 2 GANC and 1 GPNC for male partners, and sessions for caregivers was developed in line with the national and WHO recommendation. This model found a feasible approach that involved partners and caregivers in the process and increased MNCH and social support during the voyage of the pregnancy journey. Bangladesh J Obstet Gynaecol, 2022; Vol. 37(1): 14-23